« Couto Mixto » : ombilic et limbe ibérique - Benito Barja (Catalonia)
Germs and ambivalences of the symbolic capitality of Couto Mixto, a historic enclave between Spain and Portugal, symbolizing through its historical destiny and its current rediscovery, an Iberian continuum and the buried conflicts of Galician identity. From the smuggling republic to the Iberian sanctuary of the Galicia-North Euroregion of Portugal, the metamorphoses of Couto are those of a ghost who continues to overwhelm the dominant order of his time.